Organogermanium suppresses cell death due to oxidative stress in normal human dermal fibroblasts - Takeda, Tomoya; Doiyama, Sota; Azumi, Junya; Shimada, Yasuhiro; Tokuji, Yoshihiko; Yamaguchi, Hiroaki; Nagata, Kosuke; Sakamoto, Naoya; Aso, Hisashi; Nakamura, Takashi (Scientific reports, 2019)
Reactive oxygen species (ROS) are very harmful to dermal cells, and it is thus important to develop cosmetics that protect the skin from ROS and other stimuli. Repagermanium is a synthetic water-soluble organogermanium polymer, and in this study, we attempted to visualize the incorporation of germanium into normal human dermal fibroblasts (NHDFs) using isotope microscopy. In addition, the content of 3-(trihydroxygermyl)propanoic acid (THGP), a hydrolyzed monomer of repagermanium, in NHDFs was determined through liquid chromatography mass spectrometry (LC-MS/MS), and the dose-dependent incorporation of THGP was confirmed. We then evaluated the preventive effects of THGP against ROS-induced NHDF death and confirmed the observed preventive effects through gene profiling and expression analysis. The addition of 0.59–5.9 mM THGP reduced cell death resulting from ROS damage caused by the reaction between xanthine oxidase and hypoxanthine and the direct addition of H 2 O 2 . Furthermore, this study provides the first demonstration that the effect of THGP was not due to the direct scavenging of ROS, which indicates that the mechanism of THGP differs from that of general antioxidants, such as ascorbic acid. The gene profiling and expression analysis showed that THGP suppressed the expression of the nuclear receptor subfamily 4 group A member 2 ( NR4A2 ) gene, which is related to cell death, and the interleukin 6 ( IL6 ) and chemokine (C-X-C motif) ligand 2 ( CXCL2 ) genes, which are related to the inflammatory response. Furthermore, the production of IL6 induced by H 2 O 2 was suppressed by the THGP treatment. Our data suggest that the preventive effect of THGP against ROS-induced cell death is not due to antioxidant enzymes or ROS scavenging.